Effectiveness of Blended Learning Model-Based on “Kutub Al-Tis’ah” Application in Improving Students’ Critical Thinking in Hadith Study Courses - Channa, Lilik (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2022)
This study aims to analyze the differences in students’ critical thinking skills improvement between students that joined the Blended Learning model based on the Kutub al-Tis’ah and students who get the ordinary learning model. This study uses a quasi-experimental method with purposive sampling. The research samples were two classes from the Architecture Study Program of the State Islamic University of Sunan Ampel Surabaya in 2020/2021. Experiment class was a class with Blended Learning model based on the Kutub al-Tis’ah whether the conventional class was control class. The Blended model is effective if the post-test score of the Experiment class is better than the Control class. The results of the study showed that the average post-test value for the Experiment class was 90,32 with a variance of 6,799 and the Conventional class had an average value of 65,81 with a variance of 5,872. The hypothesis test of the similarity of the two post-test data averages was carried out through a normality test whose calculation results using Kolmogorov-Smirnov and Spiro-Wilk showed the post-test values for both the Experimental class and Control class were normally distributed with Sig 0,200 > =0,05. While the homogeneity test of the calculation results using the Levene test showed that the post-test value of both the Experiment class and the Control class was homogeneous with Sig 0,206 > = 0,05. While the statistical test calculation results obtained a value of Sig 0.00 < = 0.05, which means rejecting H0. The average post-test value for the Experiment class is greater than the average post-test value for the Control class that means the blended learning model based on the Kutub al-Tis’ah application is effective for improving students’ critical thinking for Hadith Studies courses.